ANFIS BASED BIDIRECTIONAL DC/DC CONVERTER WITH DUAL-BATTERY ENERGY STORAGE FOR HYBRID ELECTRIC VEHICLE SYSTEM - Dr. Dondapati. Ravi Kishore, Praveen Kumar Indupalli (International Journal of Control and Automation, 2020)
The consideration toward the improvement of different new forms of bidirectional DC to DC converters has gotten so fundamental inside the ongoing years on account of their necessity in Cross breed electric fueled engines, inexhaustible force structures, instructive investigations and other modern applications. Regarding the matter of this present need, the proposed Bi-Directional DC to DC converter (BDC) is executed as an interface among a prime vitality Energy Source (ES1), an assistant power stockpiling Energy Source (ES2), and a dc-transport link of different voltage stages, for use of the equivalent in the Cross breed electric vehicle frameworks. The proposed converter can act in a stage up mode (i.e., low-voltage dual source powering mode) and a stage down mode (i.e., high-voltage dc bus energy-regenerating mode), each with bidirectional force drift control and a Buck/Boost mode where the adaptation can autonomously oversee vital power transferability between the two low-voltage sources (i.e., low-voltage dual-source Buck/Boost mode). Thus, the circuit arrangement, activity, predictable state investigation, and Feedback control of the proposed BDC are represented with its detailed description of 3 methods of working where the computer based intelligence procedure of Versatile Artificial Neuro-Fuzzy Inference System (ANFIS) is utilized for delivering the highest quality level control of band pulses to improve the working ability. Inside the ANFIS approach, the slip-up voltage and exchange error voltage are given as information sources and thus the ANFIS controller is utilized to diminish the cost and pass on the upgraded advantage levels. It is noticeable that the usage of the proposed controller improves the productivity of the system and decrements the voltage drop over the exchange of energy activity. The proposed ANFIS strategy with bidirectional converter topology implemented in MATLAB/Simulink running stage and the yield generally speaking as execution is examined.